An app for personal searches:more-private, non-volatile searches with stigmergic inspiration - Marques, Artur (2018)
Web searching has long become a ubiquitous behavior amongst Internet users. Much has been changing: odds are that the thousands of results of yesterday have become millions of results today, but did that significant jump in quantity translate to an increase in the perceived results' quality and their applications? Some users might feel personalization efforts as stereotypification or even as inaccurate biases; they may also beware that every click on every search result may reinforce and contribute to (in)accurate representation of them - and would prefer searching without tracking. "Personal Searcher" is a work-in-progress app that makes it possible to search more anonymously. It also makes it possible to keep a private local-only history of one's searches and build personal ranking systems based on that history and other data. The goal is to benefit from local offline personalization, but search online as anonymously as possible.